Independent Effects of Species Removal and Asynchrony on Invariability of an Intertidal Rocky Shore Community - Fica-Rojas, Eliseo; Catalán, Alexis M.; Broitman, Bernardo R.; Pérez-Matus, Alejandro; Valdivia, Nelson (Frontiers in Ecology and Evolution, 2022)
Ecological stability depends on interactions between different levels of biological organization. The insurance effects occur when increasing species diversity leads to more temporally invariable (i.e., more stable) community-level properties, due in part to asynchronous population-level fluctuations. While the study of insurance effects has received considerable attention, the role of dominant species that contribute with particular functional traits across different level of organizations is less understood. Using a field-based manipulative experiment, we investigated how species richness and different types of parameters at the population level, such as the invariability of dominants, population invariability, and population asynchrony, influence the community invariability. The experiment involved the repetitive removal of the canopy forming alga Mazzaella laminarioides (hereafter “Mazzaella”) during 32 months in two rocky intertidal sites of northern-central Chile. We predicted that the invariability of dominants enhances community invariability, that the effect of multispecies population-level parameters on community invariability are dependent on species richness, and that subdominant algae are unable to fully compensate the loss of canopies of the dominant species. Biomass of algae and mobile invertebrates was quantified over time. We observed independent effects of Mazzaella removal and community-wide asynchrony on community invariability. While canopy removal reduced community invariability, population asynchrony boosted community invariability regardless of the presence of canopies. In addition, filamentous and foliose algae were unable to compensate the loss of biomass triggered by the experimental removal of Mazzaella. Canopy removal led to a severe decrement in the biomass of macrograzers, while, at the same time, increased the biomass of mesograzers. Asynchrony stemmed from compensatory trophic responses of mesograzers to increased abundances of opportunistic algae. Thus, further work on consumer-resource interactions will improve our understanding of the links between population- and community-level aspects of stability.